2002
DOI: 10.1034/j.1600-0536.2002.460504.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the autoxidation and sensitizing capacity of the fragrance chemical linalool, identifying a linalool hydroperoxide

Abstract: Fragrances are among the most common causes of allergic contact dermatitis. The two monoterpenes linalool and d-limonene are the most frequently incorporated fragrance chemicals in scented products. Previous studies on d-limonene show that this monoterpene oxidizes on air exposure (autoxidation) and that allergenic oxidation products are formed. Due to structural similarities, linalool might also form allergenic oxidation products on air exposure. The aim of the present study was to study the autoxidation of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 22 publications
(25 reference statements)
6
122
0
1
Order By: Relevance
“…The observation that contaminants or degradation products, but not the parent compound, are responsible for skin allergenicity has already been reported for other families of chemicals [8,23,24,25]. In perfume products, d -limonene and linalool are unreactive molecules devoid of sensitizing properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that contaminants or degradation products, but not the parent compound, are responsible for skin allergenicity has already been reported for other families of chemicals [8,23,24,25]. In perfume products, d -limonene and linalool are unreactive molecules devoid of sensitizing properties.…”
Section: Discussionmentioning
confidence: 99%
“…In perfume products, d -limonene and linalool are unreactive molecules devoid of sensitizing properties. However, upon air exposure, d -limonene and linalool give rise to oxidation products which behave as contact sensitizers [24] and can induce ACD.…”
Section: Discussionmentioning
confidence: 99%
“…European legislators have become increasingly aware of the allergenic properties of many common essential oil constituents, and in 2003, the 7th Amendment to the European Cosmetic Directive required that cosmetic products containing any of 26 natural products, including linalool, be labeled as potentially allergenic [20]. While linalool itself may have limited allergenic properties, it can auto-oxidize upon air exposure into a hyperoxide species [21] which can lead to contact allergy responses in mice [22]. In a study of 1511 dermatitis patients, auto-oxidized linalool was shown to induce allergenic responses in 1.3 % of those tested, with 1.1 % of patients sensitive to the linalool hyperoxide fraction, using patch tests [23].…”
Section: Studies In Human Subjectsmentioning
confidence: 99%
“…Due to the high susceptibility of VO to photo and thermal oxidation, it is very common for appearance L. Bajerski, L. R. Michels, L. M. Colomé, E. A. Bender, R. J. Freddo, F. Bruxel, S. E. Haas 348 modification and allergic reactions to appear, caused under the skin by formulations with these compositions (Vigan, 2010;Hammer et al, 2006;Sköld et al, 2002;Neumann, Garcia, 1992). Therefore, the safety of the active elements and the use is limited to increase the concentration of these oils in the formulations.…”
Section: Introductionmentioning
confidence: 99%